Síntese de precursor de sesquiterpenos ciclopentanóides - Magalhães Júnior, Elizeu de Souza (2015)
The organic synthesis program in our laboratory is based on the use of natural and abundant monoterpenes isolated from Brazilian essential oils as raw material of biologically active natural compounds and greater structural complexity. In this context this research project aims to use limonene(essential oil isolated from the peel of citrus fruits) as a starting material for the preparation of synthetic intermediates that may reach the monoterpenesdesignatedPlinol. Somesynthesisare describedin the literaturefor thePlinol, however, make use oflow abundantstarting material.ThemonoterpenePlinolA can bean interestingprecursor forthe preparation ofsesquiterpeneswith antifungalactivitycalledChokol. The suggestedsynthetic route(Figure 12)proved to be viable toobtain(1S, 2S, 5R)-5-methyl-2-(prop-1-en-2-il) -6-oxabicyclo [3.1.0] hexane-1-carbaldehyde (17), however, the royalopening andstereoselectiveof epoxide(17) can not becompletedwith success. In order todetermine thestereochemistry of theintermediatessynthesized, NMR experimentswere performed, as; 1H,13CNMRandNOEeffect, together with analysisof computationalcalculationsof molecular modelingandNMRproperties